Intrinsic post‐ejaculation sperm ageing does not affect offspring fitness in Atlantic salmon. (7th February 2020) - Hotzy, Cosima; Xuhui, Bao; Larva, Tuuli; Immler, Simone
Abstract: Post‐meiotic sperm ageing, both before ejaculation and after ejaculation, has been shown to negatively affect offspring fitness by lowering the rate of embryonic development, reducing embryonic viability and decreasing offspring condition. These negative effects are thought to be caused by intrinsic factors such as oxidative stress and ATP depletion or extrinsic factors such as temperature and osmosis. Effects of post‐ejaculation sperm ageing on offspring fitness have so far almost exclusively been tested in internal fertilizers. Here, we tested whether intrinsic post‐ejaculation sperm ageing affects offspring performance in an external fertilizer, the Atlantic salmon Salmo salar . We performed in vitro fertilizations with a split‐clutch design where sperm were subjected to four post‐ejaculation ageing treatments. We varied the duration between sperm activation and fertilization while minimizing extrinsic stress factors and tested how this affected offspring fitness. We found no evidence for an effect of our treatments on embryo survival, hatching time, larval standard length, early larval survival or larval growth rate, indicating that intrinsic post‐ejaculation sperm ageing may not occur in Atlantic salmon. One reason may be the short life span of salmon sperm after ejaculation. Whether our findings are true in other external fertilizers with extended sperm activity remains to be tested. Abstract : Early offspring development amnd growth is not affected by pot‐ejaculation sperm ageing in the Atlantic salmon.